2021
DOI: 10.1029/2021ja029202
|View full text |Cite
|
Sign up to set email alerts
|

Explicit IMF By‐Dependence in Geomagnetic Activity: Quantifying Ionospheric Electrodynamics

Abstract: The physical mechanism of the explicit B y -effect has so far remained poorly understood. It is well known that IMF B y plays important roles in several magnetospheric and ionospheric dynamics. For example, IMF B y affects the geometry of the dayside reconnection (Park et al., 2006;Sonnerup, 1974;Trattner et al., 2012) and exerts magnetic stress on opened field lines, leading to dawn-dusk asymmetries in magnetospheric

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 62 publications
3
33
2
Order By: Relevance
“…Regarding the explicit IMF B E y effect in a given hemisphere, our results are in agreement with several other previous studies (e.g., Holappa & Mursula, 2018;Holappa et al, 2020Holappa et al, , 2021Laundal et al, 2018;Ohma et al, 2021;Smith et al, 2017, references therein). Using satellite measurements, Smith et al (2017) E y effect on the high latitude ionospheric currents is not yet known.…”
Section: Summary Discussion and Conclusionsupporting
confidence: 93%
See 3 more Smart Citations
“…Regarding the explicit IMF B E y effect in a given hemisphere, our results are in agreement with several other previous studies (e.g., Holappa & Mursula, 2018;Holappa et al, 2020Holappa et al, , 2021Laundal et al, 2018;Ohma et al, 2021;Smith et al, 2017, references therein). Using satellite measurements, Smith et al (2017) E y effect on the high latitude ionospheric currents is not yet known.…”
Section: Summary Discussion and Conclusionsupporting
confidence: 93%
“…Using FAC measurements from AMPERE, Holappa et al. (2021) found stronger R1 and R2 FACs for By+ than for By in the NH winter, and for By than for By+ in the SH winter for the same level of solar wind driving. Ohma et al.…”
Section: Summary Discussion and Conclusionmentioning
confidence: 99%
See 2 more Smart Citations
“…Liou et al, 2001;Liou & Newell, 2010;Østgaard et al, 2011). Recent studies have also shown that auroral electrojets (Friis-Christensen et al, 2017;Holappa & Mursula, 2018;Holappa et al, 2021;Smith et al, 2017), auroral oval size (Reistad et al, 2020), energetic electron precipitation (Holappa et al, 2020) and substorm occurrence frequency (Ohma et al, 2021) respond differently to solar wind forcing, depending on the sign of IMF 𝐴𝐴 𝐴𝐴𝑦𝑦 and the dipole tilt angle (or season). For a fixed value of 𝐴𝐴 Φ𝐷𝐷 , the above parameters are greater for 𝐴𝐴 𝐴𝐴𝑦𝑦 > 0 than for 𝐴𝐴 𝐴𝐴𝑦𝑦 < 0 during negative dipole tilt (NH winter and SH summer).…”
Section: The Presence Of An Imfmentioning
confidence: 99%